Flip‐flop organization in the chloroplast genome of Capsosiphon fulvescens (Ulvophyceae, Chlorophyta). Issue 1 (18th December 2018) - Kim, Dongseok; Lee, JunMo; Choi, Ji Won; Yang, Ji Hyun; Hwang, Il‐Ki; Yoon, Hwan Su
Abstract : To better understand organelle genome evolution of the ulvophycean green alga Capsosiphon fulvescens, we sequenced and characterized its complete chloroplast genome. The circular chloroplast genome was 111, 561 bp in length with 31.3% GC content that contained 108 genes including 77 protein‐coding genes, two copies of rRNA operons, and 27 tRNAs. In this analysis, we found the two types of isoform, called heteroplasmy, were likely caused by a flip‐flop organization. The flip‐flop mechanism may have caused structural variation and gene conversion in the chloroplast genome of C. fulvescens . In a phylogenetic analysis based on all available ulvophycean chloroplast genome data, including a new C. fulvescens genome, we found three major conflicting signals for C. fulvescens and its sister taxon Pseudoneochloris marina within 70 individual genes: (i) monophyly with Ulotrichales, (ii) monophyly with Ulvales, and (iii) monophyly with the clade of Ulotrichales and Ulvales. Although the 70‐gene concatenated phylogeny supported monophyly with Ulvales for both species, these complex phylogenetic signals of individual genes need further investigations using a data‐rich approach (i.e., organelle genome data) from broader taxon sampling.